Transparência no processo de vacinação da Covid-19: um estudo nos municípios da Quarta Colônia de Imigração Italiana - Rosso, Cíntia Bisognin (2023)
In December 2019, a new outbreak of infections emerged in China, in Wuhan, Hubei Province. In 2020, the disease named Covid-19 (short for Coronavirus Disease 2019) was declared a pandemic by the World Health Organization (WHO), subsequently announced as a Public Health Emergency of International Concern. Since then, the pandemic has been a global public health emergency, requiring coordinated efforts to address its impacts. Vaccination has emerged as one of the most effective interventions in preventing and controlling the spread of the virus. However, given the complexity and rapid spread of the virus, significant challenges have arisen in defining appropriate strategies to address the crisis. In this context, it is crucial for governments to encourage immunization and ensure easy access to clear and reliable information about the Covid-19 vaccination process. This study aimed to investigate transparency in the Covid-19 vaccination process in the municipalities of the Fourth Colony of Italian Immigration, focusing on compliance with the requirements of the State Audit Court of Rio Grande do Sul (TCE-RS) and the citizens' perception of the different phases of the vaccination campaign. The research employed documentary analysis and field research with a qualitative approach. The sample covered the nine municipalities of the Fourth Colony of Italian Immigration, a region located in the center of the state of Rio Grande do Sul. Data for the analysis were collected from the websites of these municipalities, and 472 questionnaires were administered to residents of the studied municipalities. The data were then analyzed using SWOT and 5W2H management tools to identify problems and propose solutions for weaknesses and threats identified in the analysis, respectively. The results revealed that, overall, the studied municipalities are adopting transparent practices by disclosing vaccination campaign data on their websites. However, challenges related to information updates, accessibility, and full compliance with TCE-RS requirements were identified. These obstacles can hinder citizens' access to official information and affect the efficiency of the vaccination process. It is recommended that municipal managers adopt strategies to enhance communication between the government and the population, thereby avoiding the spread of misinformation. Additionally, solutions are proposed to address the identified problems, aiming to improve the efficiency of public administrations and promote transparency in the municipalities of the Fourth Colony of Italian Immigration. However, it is important to consider the limitations of this study, such as the restricted sample size limited to the studied municipalities. Future research may include additional variables and regions for a comprehensive analysis of public transparency, with the goal of improving public governance in different regions of Rio Grande do Sul.